A novel approach for biomechanical spine analysis: Mechanical response of vertebral bone augmentation by kyphoplasty to stabilise thoracolumbar burst fractures. (June 2016) - Germaneau, A.; Vendeuvre, T.; Saget, M.; Doumalin, P.; Dupré, J.C.; Brémand, F.; Hesser, F.; Couvertier, M.; Brèque, C.; Maxy, P.; Roulaud, M.; Monlezun, O.; et al.
Abstract: Kyphoplasty has been shown as a well-established technique for spinal injuries. This technique allows a vertebral bone augmentation with a reduction of morbidity and does not involve any adjacent segment immobilisation. There is a lack of biomechanical information resulting in major gaps of knowledge such as: the evaluation of the "quality" of stabilisation provided by kyphoplasty as a standalone procedure in case of unstable fracture. Our objective is to analyse biomechanical response of spine segments stabilised by Kyphoplasty and PMMA cement after experiencing burst fractures. Six fresh-frozen cadaveric spine specimens constituted by five vertebra (T11-L3) and four disks were tested. A specific loading setup has been developed to impose pure moments corresponding to loadings of flexion–extension, lateral bending and axial rotation. Tests were performed on each specimen in an intact state and post kyphoplasty following a burst fracture. Strain measurements and motion variations of spinal unit are measured by a 3D optical method. Strain measurements on vertebral bodies after kyphoplasty shows a great primary stabilisation. Comparisons of mobility and angles variations between the intact and post kyphoplasty states do not highlight significant difference. Percutaneous kyphoplasty offers a good primary stability in case of burst fracture. Kinematics analysis during physiological movements shows that this stabilisation solution preserve disk mobility in each adjacent spinal unit.